Cecal Ligation and Puncture-Induced Sepsis Promotes Brown Adipose Tissue Inflammation Without Any Impact on Expression of Thermogenic-Related Genes - Moreno-Navarrete, José María; Comas, Ferran; de Jager, Vincent; Fernández-Real, José Manuel; Bouma, Hjalmar R. (Frontiers in Physiology, 2021)
Background and Aims: The negative effects of chronic low-level inflammation on adipose tissue physiology have been extensively demonstrated, whereas the effects of acute inflammation are less studied. Here, we aimed to investigate the effects of sepsis-induced acute inflammation on gene expression markers of brown and white adipose tissue functionality. Methods: Brown adipose tissue (BAT) and perirenal white adipose tissue (prWAT) gene expression markers were analyzed in cecal ligation and puncture (CLP)-induced sepsis mice model. Results: CLP-induced sepsis attenuated expression of adipogenesis-related genes, in parallel to increased Tnf, Il6, and Ltf gene expression in prWAT. In contrast, CLP-induced sepsis resulted in increased expression of pro-inflammatory genes (Il6, Ltf, and Lbp) in BAT, without affecting expression of genes encoding for thermogenic activity. Conclusion: Sepsis promotes both prWAT and BAT inflammation, associated with reduced adipogenesis-related gene expression in prWAT, without significant effects on BAT thermogenic genes.